N-cyclohexyl-2-[5-(4-pyridyl)-4-(p-tolyl)-4H-1,2,4-triazol-3-ylsulfanyl]-acetamide dihydrate - Dincer, Muharrem; Ozdemir, Namik; Cetin, Ahmet; Keser, Tekin; Buyukgungor, Orhan (Int Union Crystallography, 2006)
In the title compound, C22H25N5OS center dot 2H(2)O, the molecules are stacked in columns running along the b axis. In this arrangemant, the molecules are linked to each other by a combination of one two-centre N-(HO)-O-... hydrogen bond and four two-centre O-(HO)-O-... hydrogen bonds containing two types of ring motif, viz. R-4(4)(10) and R-3(3)(11). In the crystal structure, centrosymmetric pi-pi interactions between the triazole rings, with a distance of 3.691 (2) angstrom between the ring centroids, also affect the packing of the molecules.
Keywords: Spin-Transition